Communication Across Cultures: From Cultural Awareness to Reconciliation of the Dilemmas - Vincent Merk (Fondazione Eni Enrico Mattei (FEEM), 2003)
In this globalising world there is a growing need for understanding different types and forms of interaction between people in intercultural environments, i.e. working places, cities, etc. This implies that people refer more and more to various communication models and practices to fully master communication across cultures. These models ultimately lead to applying best practices in intercultural communication. One of the most popular models in the one developed by Trompenaars & Hampden-Turner. In this paper we first review the concept of culture related to this model. Second, we present the 7 dimensions of the model. Finally, we review the reconciliation theory as presented by Hampden-Turner & Trompenaars.
Keywords: Z10; 330; Intercultural communication; Reconciliation model; Dilemmas; Intercultural context